Optical MEMS based on silicon-on-insulator (SOI) for monolithic microoptics - Noell, Wilfried; Sun, Winston; de Rooij, Nicolaas F.; Herzig, Hans-Peter; Manzardo, Omar; Dändliker, René (My University, 2002)
Microelectromechanical systems (MEMS) combined with optical components add optical functionality to devices and lead to the terms optical MEMS or MOEMS. The underlying technology of the presented devices is silicon-on-insulator (SOI) based batch fabrication, which delivers small, reliable and lasting monolithic bulk silicon structures for commercial devices with the advantage of being very insensitive to temperature changes. The particular strength of the technology is monolithic horizontal and vertical micromirrors for a variety of applications.
Keywords: microstructure devices; couplers; switches; and multiplexers; mirrors; optomechanics